Teknik Instruksional Pertanyaan di Tahap Deciding the Study Group the Way of Collecting Data and Data AnalysisProject Based Learninguntuk Meningkatkan Skor Crosslink pada Concept Map Siswa - Nina Hardiana; Sri Widoretno; Nurmiyati Nurmiyati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
Abstract: This research aimed to calculate the crosslink score in concept map through the implementation of instructional technique formed as teacher’s questions in the stage of study group the way of collecting data and data analysis in project-based learning. This research was a classroom action research with the research subject of 34 students in X MIPA of Senior High School. The research procedure was including: planning, lesson plan completed with assessment, acting, observing and reflecting.  The validity test was using triangulation method that consisted of verification to the crosslink in concept map using expert concept mam, documentation of the concept map made by the students and interview to present the understanding of relation between concepts that had a different hierarchy and students’ creativity. The data collection was using concept map in the end of the lesson. Data reduction used to choose the data completion, data interpretation and conclusion based on the complete crosslink score. Data analysis was using descriptive-qualitative. The result of this research shows that crosslink score improves in every cycle. The average of crosslink score in pre-research to cycle II were 0,269%; 5,1470% dan 18,043%. So, the use of instructional technique as teacher’s questions in the stages of deciding the study group the way of collecting data and data analysis improving crosslink score in concept map individually and classically.